Rational Prescribing of Pancreatic Enzymes for Patients with Pancreatic Cancer - Mary Acelle G. Garcia; Syed Imam; Ursula K. Braun; Leanne K. Jackson (MDPI AG, 2024)
Most patients with pancreatic cancer at some point present with symptoms related to exocrine pancreatic insufficiency (EPI). These include diarrhea, abdominal bloating, indigestion, steatorrhea, weight loss, and anorexia. Even though up to 80% of pancreatic cancer patients eventually present with symptoms related to exocrine pancreatic insufficiency, only 21% are prescribed pancreatic enzyme replacement therapy (PERT). Its effectiveness is also highly dependent on its proper timing of administration, and patients must be thoroughly educated about this. The impact of symptoms of EPI can lead to poorer overall well-being. Pharmacists play a crucial role in properly educating patients on the correct use of pancreatic enzyme replacement therapy. PERT is a key strategy in managing the symptoms of EPI and can improve quality of life, which is a central focus in palliative care. This treatment is profoundly underutilized in the palliative care of these patients. The objective of this review is to discuss the pharmacology, pharmacokinetics, side effects, available evidence of the effectiveness of pancreatic enzyme use for patients with pancreatic cancer, and challenges, along with proposed solutions regarding its use.